Mechanical spring technology improves running economy in endurance runners - Riess, K. J. (Journal of Human Sport & Exercise, 2014)
In recent years there has been an increase in participation in timed running events. With this increase, the motivation for individuals to run their best has motivated the running shoe industry to make design changes to traditional running foot wear in an effort to improve running economy (RE) and decrease running times. One such design change has been to incorporate mechanical springs (MS) into the midsole of the running shoe. Evaluation of this technology has yet to be performed. This study recruited 17 runners (12 male) and had them run at a submaximal steady state speed for 2 bouts of five minutes at a speed of 3.13 m/sec. The order of shoe condition was randomly assigned and the subjects ran one interval in their own running shoe (OS) and one interval in MS shoes. Metabolic data and heart rate data were averaged over the last three of the five minute efforts. No significant difference was found between MS and OS with regards to shoe weight. Running in MS resulted in lower, non-significant values for steady state ventilation and steady state heart rate. Oxygen consumption was significantly lower in MS compared to OS in both absolute (MS: 2.35 ± 0.47 L/min vs. OS: 2.40 ± 0.473 L/min, P=0.022) and relative (MS: 34.67 ± 4.35 ml/kg·min vs. OS: 35.34 ± 4.58 ml·kg-1·min-1, P=0.033) terms. Running in shoes fitted with MS technology improves running economy over OS and this technology may assist athletes achieve their best running times.